Cardioprotective effects of Ferulic acid against various drugs and toxic agents - Anandakumar Pandi; Mahto Hemanti Raghu; Naveenkumar Chandrashekar; Vanitha Manickam Kalappan (Beni-Suef University Journal of Basic and Applied Sciences, 2022)
Abstract Background Homeostatic regulation of cardiomyocytes is indispensable in maintaining the normal physiological activity of cardiac tissue. Cardiotoxicity induced by drugs may lead to cardiac abnormalities such as arrhythmia, myocardial infarction and myocardial hypertrophy. Moreover, drug-induced cardiotoxicity confines the additional use of the implicated drugs. Several studies have reported that consumption of phytochemicals on regular intervals shall protect humans against numerous diseases such as diabetes, cardiovascular disease, inflammatory diseases and cancer. Main body Ferulic acid (FA) is a plant derived polyphenol abundantly found in vegetables, fruits and grains. FA is widely known for its antioxidant, anti-inflammatory, anticancer, nephroprotective and hepatoprotective effects. FA has been well documented for its cardioprotective activity against various drugs and toxic agents as well. However, the cardioprotective action of FA have remained a challenge with regard to understanding its mechanism in health and diseases. Conclusion The main purpose of this review is to explore the cardioprotective mechanisms of FA against several drugs and chemicals to recommend further studies to investigate the potential protective effect of FA.